Implementasi Manajemen Pendidikan Karakter Religius Melalui Kegiatan Ekstrakurikuler dan Pembiasaan Keagamaan - Saipul Annur; Hartatiana Hartatiana; Ahmad Firmansyah (Studia Manageria, 2022)
The purpose of this study was to reveal the implementation of the management of students' religious character education through spiritual extracurricular activities and religious habituation at SMK Palembang. This research is a qualitative research with a qualitative descriptive approach with natural characteristics (natural setting) as a direct data source, descriptive, more concerned with the process than the results. Collecting data through observation, interview and documentation techniques. Data analysis techniques with inductive and deductive methods. The problems discussed include various implementations of religious character education management in Islamic spiritual extracurricular activities and religious habituation as well as the values ​​of students' religious character at SMK Palembang. The results showed that the implementation of religious character education management through Islamic spiritual extracurricular activities and students' religious habituation as well as character values ​​that developed at SMK Palembang has been running, this can be seen from several extracurricular activities of the Spirit in the form of symbols, talents (skills), public relations, regeneration, sports and the arts. Furthermore, there are religious habituation activities including moral guidance, giving donations, reading the Qur'an, praying in congregation, Ramadan boarding schools and zakat fitrah. The character values ​​that can be revealed through spiritual extracurricular activities and religious habituation are religious, curiosity, tolerance, respect for achievement, discipline, communicative, hard work, peace-loving, creative, fond of reading, independent, caring for the environment, democratic and responsible.